Evolving Definitions of War and Peace: A Historical Analysis of the Last Two Centuries (Mongolian Journal of International Affairs, 2024)
This study looks at the evolution of war and peace concepts from 1800 to 2024, assessing how global political shifts, technology advancements, and shifting societal standards have shaped these key concepts. By examining significant historical events and shifts in the international landscape, the study hopes to provide a complete picture of how conceptions of war and peace have evolved over time and continue to impact contemporary international relations. The study helps to provide a better grasp of these dynamic notions in our modern, interconnected world.